Come muoversi a Roma con il trasporto pubblico e il Bike Sharing - Ieradi, Michele; Perla, Annalisa; Leggeri, Flaminia; Cera, Emilio (GEOmedia, 2008)
The public transport-bike sharing integration in Rome Based on the success in Rome due to the launch of its bike sharing service (on June 13, 2008), ATAC (Rome Mobility Agency) designed and implemented the integration of paths that connect the 19 bike sharing collection points, located in the heart of Rome, with the public transport network. The resulting database has been included in a new version of the Journey Planner service, Infopoint, already available on the ATAC website, which gives users the opportunity to calculate an itinerary with public transport and if possible to combine the public transport with the bike sharing schedule.